The Symbol of Colonial Power through Urban Art: The Case of Mogadishu - Chiara Cozzatella; Vincenzo Cosentino (European Journal of Creative Practices in Cities and Landscapes)
This paper explores the historical and symbolic significance of urban structures in Mogadishu, focusing on Italian colonial and religious art. Beginning with a contextualization of Italian colonialism in Somalia, the authors analyze the impact of structural interventions, particularly the construction of the Cathedral in 1928, reflecting Italy’s attempt to Europeanize the city. The study employs three lenses—religious, architectonic-spatial, and political—to unravel the complexities of colonial urban art. The Cathedral, a focal point of the analysis, exemplifies the multifaceted strategy of legitimizing Italian presence through religious symbolism, spatial transformation, and political assertion. The paper critically examines how colonial architecture displaced local populations, reshaped the urban landscape, and reinforced power dynamics. It also underscores the lack of acknowledgment and debate in Italy regarding its colonial past, urging a reconsideration of colonial monuments as heritage or reminders of a contentious history. The authors emphasize the need for Italy to confront its colonial legacy, advocate for education on this topic, and challenge the perpetuation of colonial-era commemorations.